A Study of the Watermelon (Citrullus lanatus) Effectiveness as a Menstrual Cutter (Dysmenorhea) in Teenagers - Refi Yulia Rahmawati (Universitas Muhammadiyah Surabaya, 2022)
The purpose of the study was to see the effectiveness of the watermelon (citrullus lanatus) as a menstrual cutter (dismenorhea). The method used in this study is a deductive oenqualitative literature study in which in this study begins library studies, data retrieval, results analysis, deduction. A study found in watermelons contains potassium, vitamin c, kerbohydrate, lyopen, vitamin b6 that ACTS to reduce menstrual anxiety. Menstrual pain (dysmenorhea) is affected by the age of the dancing factor, the nutritional status of the woman, and the genetic factor. The symptoms experienced when a woman has menstrual pain (menorhea) are pain lower in her abdomen, thighs aching, nausea, dizziness, lower back pain, backache, backache, diarrhea, constipation, and fainting. Anxiety can increase the synthesis of prostaglandin along with drop levels of esogen and progesterone, and then the uterus muscle, uterine blood flow, uterine ischemia, and uterine pain resulting. It was thus obtained in the study that watermelons can help relieve menstrual pain.